2022
DOI: 10.29303/jppipa.v8i4.1820
|View full text |Cite
|
Sign up to set email alerts
|

Development of STEM Integrated Physics E-Modules to Improve 21st Century Skills of Students

Abstract: In the current era of the industrial revolution 4.0, students are required to have 21st century skills. The 21st century skills in question are students mastering the 4C skills, that are Communication, Collaboration, Critical thinking and Creativity skills. These four skills must be possessed by students to face the world in the 21st century. One of the current learning approaches that strongly supports the achievement of 21st century skills is STEM-based learning (Science, Technology, Engineering, and Mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Similar research also obtained the same results that PjBL STEM learning had an effect on science literacy (Afriana, 2022). In line with research Nilyani et al (2023) that STEM-integrated science learning has a very high influence on students' science literacy and critical thinking skills. In line with Asri et al (2021) research, which found that there was an increase in post-test results compared to pretests after the application of PjBl learning with the STEM approach.…”
Section: Figure 3 Average Results Of Student Pretest and Posttestsupporting
confidence: 84%
“…Similar research also obtained the same results that PjBL STEM learning had an effect on science literacy (Afriana, 2022). In line with research Nilyani et al (2023) that STEM-integrated science learning has a very high influence on students' science literacy and critical thinking skills. In line with Asri et al (2021) research, which found that there was an increase in post-test results compared to pretests after the application of PjBl learning with the STEM approach.…”
Section: Figure 3 Average Results Of Student Pretest and Posttestsupporting
confidence: 84%
“…Communication is a skill to express new thoughts, ideas, knowledge, or information, both in writing and orally (Greenstein, 2012). Indicators assessed on communication skills are in the form of conveying opinions and ideas appropriately (Husna, 2012), inferring information, using correct and effective sentences, and using appropriate punctuation marks (Amala et al, 2019;Nazifah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Every human being is required to have critical thinking skills; to be able to master technology, communication, collaboration; and to connect knowledge with the real world (Anggraeni & Sole, 2018). These skills become a major component to maintain the life of the people of the 21st century (Nazifah & Asrizal., 2022). The creation of 21st-century skills requires learning as a bridge.…”
Section: Introductionmentioning
confidence: 99%